2003
DOI: 10.1172/jci200316889
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant proteins A and D inhibit the growth of Gram-negative bacteria by increasing membrane permeability

Abstract: The pulmonary collectins, surfactant proteins A (SP-A) and D (SP-D), have been reported to bind lipopolysaccharide (LPS), opsonize microorganisms, and enhance the clearance of lung pathogens. In this study, we examined the effect of SP-A and SP-D on the growth and viability of Gram-negative bacteria. The pulmonary clearance of Escherichia coli K12 was reduced in SP-A–null mice and was increased in SP-D–overexpressing mice, compared with strain-matched wild-type controls. Purified SP-A and SP-D inhibited bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
154
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(170 citation statements)
references
References 49 publications
10
154
0
6
Order By: Relevance
“…Several lines of evidence suggest that the collectins increase the permeability of the surface of Hc, as we have recently demonstrated for some but not all strains of Escherichia coli (8). Incubation of yeast with both collectins increased protein leak from the organism and enhanced the access of a hydrolysis-activated fluorescent substrate to intracellular alkaline phosphatase.…”
Section: Discussionsupporting
confidence: 56%
“…Several lines of evidence suggest that the collectins increase the permeability of the surface of Hc, as we have recently demonstrated for some but not all strains of Escherichia coli (8). Incubation of yeast with both collectins increased protein leak from the organism and enhanced the access of a hydrolysis-activated fluorescent substrate to intracellular alkaline phosphatase.…”
Section: Discussionsupporting
confidence: 56%
“…2,6 SP-D enhances the in vitro production of superoxide by alveolar macrophages 7 and inhibits T-lymphocyte proliferation. 8 In both in vitro and in vivo studies, SP-D has been reported to bind to, and mediate the clearance of, apoptotic inflammatory cells by alveolar macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously that SP-A and SP-D regulate pulmonary inflammation through interaction with pattern recognition receptors, including Toll-like receptors, CD14 and MD-2 (8 -11). Pulmonary collectins also directly interact with microbes, including Escherichia coli, Klebsiella pneumoniae, Enterobacter aerogenes, and Mycoplasma pneumoniae, and inhibit their growth (12,13).…”
mentioning
confidence: 99%